The Influence of Audiovisual and Poster Education on Patient Referral Motivation to Hospitals in Dengue Hemorrhagic Fever (DHF) Cases at Husada Mulia Klakah Clinic - Ummu Latifah; Ro'isah; Marfuah (Health and Technology Journal (HTechJ), 2024)
Dengue hemorrhagic fever (DHF) is an acute infectious disease caused by the Dengue virus which is transmitted through mosquito bites. The problem that occurs at the Husada Mulia Klakah Clinic in the case of Dengue Hemorrhagic Fever (DHF) patients is that when a referral is made to the hospital, the patient is reluctant to decide to leave immediately even though the patient's condition requires a referral to get maximum service at the hospital. Patient motivation plays an important role in patient referral actions. This study aims to analyze the effect of audiovisual education and posters on the motivation to refer patients to hospital in cases of Dengue Haemorrhagic Fever (DHF). This research used a pre-experimental method with a pre and post test group design approach with a population of 25 respondents and a sample of 20 respondents. The sampling technique used accidental sampling. Data was collected using a questionnaire sheet and then analyzed using the Wilcoxon test. Based on the results of the Wilcoxon test analysis, it showed a ρ value of 0.000. The conclusion of this study shows the influence of audiovisual education and posters on the motivation to refer patients to hospital in cases of Dengue Haemorrhagic Fever (DHF) at the Husada Mulia Klakah Clinic. It is hoped that health workers will evaluate and provide education for Dengue Hemorrhagic Fever (DHF) patients who need referral and further treatment to the hospital to create motivation in patients to receive optimal treatment.